2012
DOI: 10.1134/s1070328412030086
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear complexes with the “Chinese Lantern” geometry as intermediates in the liquid-phase oxidation of dibenzyl ether with atmospheric oxygen in the presence of copper(II) carboxylates

Abstract: Reactions of copper(II) carboxylates with dibenzyl ether (DBE) gave binuclear complexes of the formula Cu 2 (µ OOCR) 4 (DBE) 2 (R = Bu t , Ph, and CF 3 ). The complexes were characterized by X ray dif fraction. The axial positions in the lantern type dimer are occupied by the coordinated DBE molecules. The complexes seem to be analogs of intermediate catalysts for the oxidation of DBE with atmospheric oxygen in the presence of transition metal complexes. When stored in air, the complex Cu 2 (µ OOCPh) 4 (DBE) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…OOC-t-Bu) 4 (L) 2 (L = THF, O(CH 2 Ph) 2 ) 17,18. Two acetonitrile molecules are differently located in axial positions (Cu−N distances of 2.197(2) and 2.222(2) Å and Cu−Cu−N angles of 155.2°and 170.5°) due to the presence of the benzene solvate molecule located quite close to one of the acetonitrile molecules.…”
mentioning
confidence: 99%
“…OOC-t-Bu) 4 (L) 2 (L = THF, O(CH 2 Ph) 2 ) 17,18. Two acetonitrile molecules are differently located in axial positions (Cu−N distances of 2.197(2) and 2.222(2) Å and Cu−Cu−N angles of 155.2°and 170.5°) due to the presence of the benzene solvate molecule located quite close to one of the acetonitrile molecules.…”
mentioning
confidence: 99%
“…According to X ray diffraction data (Fig. 1, Tables 1-3), the geometry of this cluster is similar to that found for complex 1: two Cu(II) atoms spaced at a nonbonding distance of 3.2934 (7) (4) Cu (1) (7) 1571 ( It was assumed that such a complex containing weakly basic anions (СF 3 ) 2 pz, a bridging water mole cule, and bridging acetate anions coordinated to Cu(II) ions would break down into mono or binu clear complexes during its thermolysis in DBE, which can be coordinated by copper atoms to form lantern type dimers [3].…”
Section: Resultsmentioning
confidence: 99%
“…To explain this phenomenon, we have assumed that BAc accumulation in the presence of copper(II) com plexes can follow pathways that are alternative to schemes (1) and (2), e.g., through decomposition of peroxybenzoic acid (PBAc), which is formed in the dehydration of DBE dihydroperoxide (DHP) accord ing to the scheme The schemes of the catalytic cycles of liquid phase oxidation of DBE in the presence of the metal com plexes studied, which have been proposed in the monograph [1], involve the pre coordination of DBE We have isolated and identified such complexes of the formula Cu 2 (μ OOCR) 4 (DBE) 2 (R = CF 3 , Ph, and Bu t ) using X ray diffraction for binuclear lantern type copper carboxylates [3]. We have found that low basicity DBE in the lantern type dimer is an axial ligand and that the metal-metal distance depends on the substituent in the carboxylate anion.…”
mentioning
confidence: 98%
“…10−12 In a similar manner, the treatment and recycling of ethereal solvents, including benzyl ether, by deoxygenation reactions are used to produce useful chemical products from what would otherwise be waste material. 13,14 Metal halides have also been reported as reagents for ether cleavage to give alkyl halides, where the metal acts as a halogen transfer reagent. For example, bismuth can transfer a chlorine atom to 2-methyl-and 2,5-dimethyltetrahydrofurans, where the ring is preactivated with an acyl chloride (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In sharp contrast, the reverse reaction is considered to be significantly more difficult, since deoxygenation of ethers back to alkyl halides is generally thermodynamically unfavorable due to the strength of the C–O bond and relative weakness of the C–X bond formed in the alkyl halide products, as shown in selected examples in Figure . , One notable application of such ether cleavage reactions has been the deprotection of phenol derivatives; boron tribromide is a classic reagent for the cleavage of methyl ethers of phenols as well as certain other ethers. , Other reactions with milder reagents or conditions for the cleavage of dimethyl ether and similar ethers have also been developed that tolerate a wider range of functional groups. , In addition to deprotection reactions, ether cleavage can be used in its own right in synthesis and semisynthesis from ether natural products and substrates, such as in the depolymerization of lignin, which is a critical step in biomass conversion to liquid fuels. In a similar manner, the treatment and recycling of ethereal solvents, including benzyl ether, by deoxygenation reactions are used to produce useful chemical products from what would otherwise be waste material. , …”
Section: Introductionmentioning
confidence: 99%